Molecular characteristics and Helicobacter pylori infection rates in patients with gastric cancer in Western Poland: a comparative analysis of gastrectomy specimens across two decades - Majewski, Jan; Moszyńska, Marta; Stawczyk-Eder, Kamila; Woźniak, Aldona; Dobrowolska, Agnieszka; Kaczmarek, Elżbieta; Eder, Piotr (Frontiers in Oncology, 2026)
IntroductionGastric cancer incidence and characteristics vary due to environmental factors, and technical advances facilitate early detection of the disease. This study aimed to assess whether significant socio-economic changes and technological advancements in Poland — one of the most rapidly developing countries worldwide — affected the molecular characteristics and detection rates of early gastric cancer sub-types in Western Poland.MethodsNinety-two patients undergoing gastrectomy for gastric cancer in 1998–2002 and 2016–2020 were studied. Surgical specimens were re-analyzed for histopathological features, including tumor type, grade, and stage (up-dated World Health Organization [WHO] classification). Immunohistochemical markers (Ki-67, p53, E-cadherin, CD10, CD31, bcl-2) and antigens for Helicobacter pylori (H. pylori) and Epstein-Barr virus (EBV) were evaluated. Microsatellite instability (MSI) was assessed via PMS2/MSH2 protein expression.ResultsThe groups were comparable in age and gender, with male predominance. Histological features, H. pylori and EBV colonization, and most molecular markers showed no significant differences. However, Ki-67 proliferation index significantly increased in cancers diagnosed in 2016-2020, correlating with intestinal-type tumors and p53 expression. In this group, higher Ki-67 levels were also linked to H. pylori infection, microsatellite stability, and increased angiogenesis.ConclusionsDespite advancements in H. pylori research and technology over 20 years, no improvement was observed in H. pylori-positive tumor rates or early gastric cancer detection in Western Poland. Although molecular characteristics remained largely unchanged, the increased proliferation index in recently diagnosed cancers merits further study.